Digital Marketing Innovation and Online Consumer Behavior: Implications for Brand Equity (Case Study of Coffee Consumers at the Mandala By Pass Medan Branch): Inovasi Pemasaran Digital dan Perilaku Konsumen Online: Implikasinya terhadap Ekuitas Merek (Studi Kasus Konsumen Kopi di Cabang Mandala By Pass Medan) - Crystalin Varelie; Hommy Dorthy Ellyany Sinaga; Johnny Chandra (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The shift towards the digital age has had a major impact on the fundamentals of the economy, changing the way individuals and businesses interact in trade, and shaking up existing conventional methods. Today, amid the dominance of the digital world, social media platforms have emerged as a highly efficient marketing tool for reaching audiences instantly, extensively, and at an affordable cost. This study is designed to examine in depth the impact of digital marketing strategies and consumer behavior dynamics on brand value formation, focusing on customers of Kopi Petik Mandala by Pass branch in Medan as the research subjects. The survey was conducted at the Kopi Petik location on Jl. Mandala by Pass No.71A, Tegal Sari Mandala I, Medan Denai, Medan City, North Sumatra 20226, from August to September 2025, using a purposive sampling method. The findings of this research explain how both factors, namely digital marketing strategies and consumer behaviour, influence brand strength, as shown in the multiple linear regression analysis. The results, both separately and together, show that digital marketing activities and consumer behavior trends have a positive and significant impact on brand value at Kopi Petik Mandala by Pass branch.